PENINGKATAN HASIL BELAJAR SISWA KELAS IV SD PADA MATERI INDONESIAKU KAYA BUDAYA MELALUI MEDIA PETA KERAGAMAN BUDAYA - Wulan Handayani; Nandang Budiman; Novi Ayudyaningtias (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning media is a means used so that the interaction in the implementation of learning takes place realistically so that students can receive information well. The purpose of this study was to describe process and improvement of learning outcomes of fourth grade students on the material of Indonesia's rich culture through cultural diversity maps. The research method used is collaborative classroom action research through the stages of 3 cycles. The research subjects were fourth grade students of one of the elementary schools in Bandung City in the 2022/2023 school year. The results showed that students could master the learning material presented through 3 cycles. The completeness of student learning outcomes showed as much as 30% in cycle 1, 75% in cycle 2, and 92% in cycle 3. Thus, that the improvement in the learning outcomes of grade IV students on the material of Indonesia's rich in culture through a map of cultural diversity there is a significant increase in learning outcomes, and the material of Indonesia's rich in culture can be delivered through the media of cultural diversity maps. Recommendations for further research to use cultural diversity maps on other materials.